Rare presentation of angiomatosis in the paranasal sinuses mimicking juvenile nasopharyngeal angiofibroma in a 16 year old male - Neeraj V. Suresh, BS; Viraj N. Shah, MD; David Matichak, BS; Michael K. Ghiam, MD; Luke J. Pasick, MD; Isaac J. Abecassis, MD; Ali G. Saad, MD; Jacques Morcos, MD; Zoukaa Sargi, MDMPH; Rita Bhatia, MD (Radiology Case Reports, 2022)
Rare presentation of pediatric angiomatosis of the paranasal sinus and skull base presenting mimicking juvenile nasopharyngeal angiofibroma (JNA). This is a 16-year-old male who presented to the emergency room with acutely worsening headaches, decreased visual acuity, subjective diplopia on lateral gaze, and a skull base mass centered in the sphenoid cavity. Endoscopic biopsy at an outside facility was aborted due to profuse bleeding. Upon transfer to a tertiary care center, contrast MR demonstrated a heterogeneously and avidly enhancing vascular mass centered around the sphenoid and skull base originating from the internal maxillary artery with significant bilateral extension into the adjacent paranasal sinuses, sella, and cavernous sinus. History of presentation and imaging was suggestive of JNA. Patient underwent preoperative embolization followed by endoscopic endonasal transphenoidal resection with a skull base trained otolaryngologist and neurosurgeon. Final pathology confirmed angiomatosis. This is only the second reported case of paranasal sinus angiomatosis in the literature. Angiomatosis has a high rate of recurrence and failure of timely diagnosis can lead to requirement of repeated surgical intervention. Re-operations are associated with increased costs, patient dissatisfaction, and poorer surgical/clinical outcomes. Because angiomatosis can mimic JNA, hemangiomas, or other vascular tumors, it is essential to maintain a broad differential diagnosis that includes angiomatosis when evaluating sinonasal tumors.